THE EFFECTIVENESS OF USING GOOGLE CLASSROOM IN IMPROVING STUDENT LEARNING OUTCOMES IN ENTREPRENEURSHIP COURSES - Widoretno, Yustin Setiya; Umaroh, Susi Tri (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
The rapid advancement of science and technology has transformed education, necessitating effective digital learning tools like Google Classroom, particularly during the COVID-19 pandemic. While previous studies have explored its general educational benefits, its specific effec-tiveness in vocational technical education—particularly for Entrepre-neurship courses in engineering programs—remains under-researched. This study addresses that gap by quantitatively assessing Google Class-room’s impact on 45 D4 Mechanical Engineering students at Universi-tas Negeri Surabaya. Results show that 44% of respondents strongly agree on the platform’s usability and flexibility, while 50% confirm its role in enhancing comprehension, assignment completion, and academ-ic performance in Entrepreneurship. Statistical analysis further validates these findings, with a significant t-test result (t-count = 2.365 > t-table = 2.025) demonstrating improved learning outcomes. By providing empir-ical evidence of Google Classroom’s efficacy in a vocational engineer-ing context, this study contributes novel insights to digital pedagogy literature. The findings advocate for the platform’s broader adoption in technical higher education, supporting optimized digital learning strate-gies in the industry 4.0 era.